The Impact of Business Intelligence on E-Learning at Technical University - Amani Osman Sulieman; Randa Elgaili Elsheikh HamadElniel (Qubahan Academic Journal)
This study explores the effect of Business Intelligence (BI) on the effectiveness of E-learning systems within technical universities. With the increasing metamorphosis of the world of education into a digital one, the role of BI tools in the enhancement of decision-making processes, monitoring of the students, and the improvement of academic processes have become pivotal. The study adopts a quantitative, descriptive-correlational research design involving 385 faculty members and structured questionnaires to measure the influence of BI dimensions Analytical Capability, Data Quality and Accessibility, and Infrastructure and Technical Support on E-learning metrics like Learning Outcomes, Student Engagement, and Organizational Support. Findings show strong correlations between the BI dimensions and the success of E-learning, with the greatest emphasis on Analytical Capability and Data Quality. These results highlight the importance of educational institutions strategically utilizing their data and improving their analytic frameworks rather than concentrating solely on the technical aspects of the institution’s infrastructure. The study also demonstrated that the integration of BI into educational frameworks, particularly within technical universities, improves E-learning systems by fostering personalized learning, providing proactive interventions, and much more, thus making a compelling case.